2008
DOI: 10.3341/kjo.2008.22.4.272
|View full text |Cite
|
Sign up to set email alerts
|

A Case of an Asymptomatic Intralenticular Foreign Body

Abstract: The purpose of this article is to report a case of an asymptomatic intralenticular metallic foreign body that was retained for 6 months. A 66-year-old male visited our ophthalmology department because of decreased visual acuity in his left eye 6 months after he suffered ocular trauma while mowing. He had not been treated because he did not experience any discomfort. His corrected visual acuity was 0.4. Central corneal opacity, an intralenticular metallic foreign body, and an intact posterior capsule were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…On the other hand the healing capacity of the anterior lens capsule, in contrast to the posterior capsule, is well documented and is thought to result from the presence of the subcapsular epithelium 9. If the capsule defect is small, epithelial proliferation rapidly restores its continuity, limiting the free passage of ions and fluid that may result in progressive cataract formation 10. In our patient’s case, the size of the ILFB was small and it is possible that the capsular break was small enough to heal spontaneously.…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand the healing capacity of the anterior lens capsule, in contrast to the posterior capsule, is well documented and is thought to result from the presence of the subcapsular epithelium 9. If the capsule defect is small, epithelial proliferation rapidly restores its continuity, limiting the free passage of ions and fluid that may result in progressive cataract formation 10. In our patient’s case, the size of the ILFB was small and it is possible that the capsular break was small enough to heal spontaneously.…”
Section: Discussionmentioning
confidence: 76%
“…Missed IOFBs in OGI were rare because of the relatively large size of foreign bodies and serious visual loss. However, tiny occult foreign bodies may be missed and retained in patients with small self-sealing wounds and no decreased visual acuity without complete examination [46, 14].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, IOFBs that could cause severe visual impairment are identified. However, tiny and occult foreign bodies may be missed and retained in patients with small self-sealing wounds and no decreased visual acuity without complete examination [46]. The natural progression of a retained IOFB varies depending on its size and location, the toxicity of the material, and risk of infection [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have reported a retained iron intralenticular foreign body undetected by imaging [ 6 ]. A retained iron intralenticular foreign body may remain silent for a longer period of time, even up to 60 years [ 7 ].…”
Section: Discussionmentioning
confidence: 99%